SERUMPUN SEBALAI DI SMK TUNAS HARAPAN BANGSA - Qoyim, Ibnu (Jurnal Masyarakat dan Budaya, 2010)
This article reviews a harmonious pluralistic society in Pangkalpinang, Bangka, represented by a school named Tunas Harapan Bangsa.It was already wellknown that Pangkalpinangis a city that developed by a variety of groups, in term of ethnicity, religion and culture. The plurality is a social reality that shaped Pangkalpinangpeople to develop awareness among themselves about the importance of unity and harmonious living in their ecological settlement. They fully settled in a region with a “unity in diversity” which they express in a term known as “Serumpun Sebalai”, which mean “one place for various groups”. The term describes a complete unity among different ethnic, religious and cultural groups. Such condition is a dreamed reality of many Indonesians, something that is not easily realized elsewhere in Indonesia. Keywords: serumpun sebalai, SMK Tunas Harapan Bangsa, pluralistic society